THE GEOECONOMIC COMPONENT OF THE GRAND STRATEGY OF THE UNITED STATES IN THE INTERWAR PERIOD - Marjanovic, Boban (Political Review, 2025)
U.S. foreign policy, from the Paris Peace Conference to the Geneva Disarmament Conference (1932–1934), is commonly viewed through the lens of a isolationist strategy. The reasons for this are methodological in nature, given that the greatest attention has generally been devoted to political processes but without their connection to economic factors. The regulation of American war loans and financial policy has been a rare subject of research. This paper is based on the argument that the geoeconomic component was the central element of the U.S. grand strategy in the interwar period and that it preceded political and military strategy. By applying economic instruments, the U.S. leadership sought to secure primacy in relations with Europe and create conditions for the United States to assume a leading role. The Washington leadership used war loans granted to European states during World War I and took the lead in regulating German reparations to achieve geopolitical objectives. For this reason, the paper examines the theoretical foundations of geoeconomics and the role of this component in grand strategic policy.
Keywords: grand strategy; geoeconomics; U.S.; war debts; reparations; trade agreements